2010
DOI: 10.4319/lo.2010.55.6.2339
|View full text |Cite
|
Sign up to set email alerts
|

Degree of oligotrophy controls the response of microbial plankton to Saharan dust

Abstract: To determine the effects of Saharan dust on the abundance, biomass, community structure, and metabolic activity of oceanic microbial plankton, we conducted eight bioassay experiments between ca. 30uN and 30uS in the central Atlantic Ocean. We found that, although bulk abundance and biomass tended to remain unchanged, different groups of phytoplankton and bacterioplankton responded differently to Saharan dust addition. The predominant type of metabolic response depended on the ecosystem's degree of oligotrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
172
2
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(212 citation statements)
references
References 60 publications
32
172
2
6
Order By: Relevance
“…Additionally, studies that did assess community structure in response to dust typically focused on ≥48 h after dust addition, which could miss taxa that mount a more rapid response (31,36). Finally, much of the recent work in this area has examined response in experimental microcosms and mesocosms (15,31,36), with few studies able to capture in situ response to natural dust events. In this study, evidence from both experimental manipulations and in situ time course observations demonstrated that opportunistic heterotrophic genera like Vibrio mount a robust and rapid growth response to dust addition and potentially play an important, but currently largely unexplored, role in the cycling of Fe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, studies that did assess community structure in response to dust typically focused on ≥48 h after dust addition, which could miss taxa that mount a more rapid response (31,36). Finally, much of the recent work in this area has examined response in experimental microcosms and mesocosms (15,31,36), with few studies able to capture in situ response to natural dust events. In this study, evidence from both experimental manipulations and in situ time course observations demonstrated that opportunistic heterotrophic genera like Vibrio mount a robust and rapid growth response to dust addition and potentially play an important, but currently largely unexplored, role in the cycling of Fe.…”
Section: Discussionmentioning
confidence: 99%
“…These recent investigations of heterotrophic response to dust-associated nutrients as well as the direct effect of Fe addition to marine waters generally measured bulk parameters (such as total bacterial abundance, bacterial respiration, or bacterial production), which could potentially fail to recognize community shifts and mask the emergence of functionally important taxa that can rapidly respond to nutrients (19,31,36). Additionally, studies that did assess community structure in response to dust typically focused on ≥48 h after dust addition, which could miss taxa that mount a more rapid response (31,36). Finally, much of the recent work in this area has examined response in experimental microcosms and mesocosms (15,31,36), with few studies able to capture in situ response to natural dust events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of atmospheric deposition in the surface ocean may vary with the biogeochemical state of the receiving waters, [95] and result in fundamental differences in the response of the microbial community structure (e.g. stimulation of heterotrophy v. autotrophy [96] ), and so vertical carbon export and nutrient cycling. Particle deposition to the ocean can also provide ballast for sinking particles, [97] which may augment the export flux resulting from increased nutrient supply by atmospheric deposition.…”
Section: Atmospheric Nutrient Supply To the Surface Oceanmentioning
confidence: 99%